2020
DOI: 10.1021/acs.jchemed.0c00642
|View full text |Cite
|
Sign up to set email alerts
|

Online Teaching Practices and Strategies for Inorganic Chemistry Using a Combined Platform Based on DingTalk, Learning@ZJU, and WeChat

Abstract: Due to the COVID-19 outbreak, an online inorganic chemistry course for engineering students was set up at Zhejiang University for the 2020 spring semester. In this study, we will be using this course as an example of how to offer efficient methods for online teaching in chemistry. Applications such as DingTalk, WeChat, and the Learning@ZJU Web site were combined to establish a network platform to smoothly carry out this course. Personal insights on high-quality online teaching for inorganic chemistry are also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…He also discussed his personal views on highquality online teaching of inorganic chemistry. e study found that these students performed very well in the two exams, which confirmed that the online platform and strategies established by Xiao C are very effective for teaching and learning [4]. Frias and Martínez discussed potential conflicts between network neutrality regulations and future 5G services, especially with regard to network virtualization.…”
Section: Introductionmentioning
confidence: 56%
“…He also discussed his personal views on highquality online teaching of inorganic chemistry. e study found that these students performed very well in the two exams, which confirmed that the online platform and strategies established by Xiao C are very effective for teaching and learning [4]. Frias and Martínez discussed potential conflicts between network neutrality regulations and future 5G services, especially with regard to network virtualization.…”
Section: Introductionmentioning
confidence: 56%
“… 13 DingTalk is a free popular learning platform that can readily be used by students in China and in other countries. 15 Our experience showed that online teaching with DingTalk presented several advantages. Firstly, it is a free and effective online teaching tool for international students.…”
Section: Resultsmentioning
confidence: 92%
“…In the spring semester of 2020, our online teaching of the molecular biology course with rain class for Chinese students and the biochemistry course for international students both experienced serious network conjestion 13 . DingTalk is a free popular learning platform that can readily be used by students in China and in other countries 15 . Our experience showed that online teaching with DingTalk presented several advantages.…”
Section: Resultsmentioning
confidence: 99%
“…Lecturers had to create online practical skills training. With limited access to clinical, field-based, or laboratory settings, lecturers taught only the conceptual aspects of practical skills through online guest lectures, live skill demonstration sessions, video recordings of field trips, conceptual application exercises, or by substituting skills practice with new theoretical topics (Chan et al, 2020;de Luca et al, 2021;Dietrich et al, 2020;Dodson & Blinn, 2021;Garcia-Alberti et al, 2021;Gomez et al, 2020;Xiao et al, 2020). Only Page 7 of 23 Koh and Daniel Int J Educ Technol High Educ (2022) 19:56 in three studies about forest operations, ecology, and nursing was it possible to practice hand skills in alternative locations such as public parks and students' homes (Dodson & Blinn, 2021;Gerhart et al, 2021;Palmer et al, 2021).…”
Section: Online Practical Skills Trainingmentioning
confidence: 99%
“…Outcomes: Online practical skills training had different effects on learning experiences, test scores, and attendance/completion rates. Students can attain expected test scores through conceptual learning of practical skills (Garcia-Alberti et al, 2021;Gomez et al, 2020;Xiao et al, 2020). However, not all students had positive learning experiences as some appreciated deeper conceptual learning, but others felt disconnected from peers, anxious about losing hand skills proficiency, and could not maintain class attendance (de Luca et al, 2021;Dietrich et al, 2020;Gomez et al, 2020).…”
Section: Online Practical Skills Trainingmentioning
confidence: 99%